Comportamiento de la infección por SARS-COV 2 en relación a los valores de CT en pruebas RT-PCR del personal de salud médico de la Libertad - Pampa Espinoza, Juan Jose Eleazar (2022)
To describe the behavior of the SARS-COV 2 infection in relation to the CT values in RT-PCR tests of the medical health personnel of La Libertad. Material and method: A descriptive, cross-sectional, retrospective study was designed. The population was made up of doctors with a diagnosis of COVID-19 infection using an RT-PCR test according to the database of the Medical College of Peru - Regional Council I La Libertad, from March 2020 to February 2021. Sociodemographic and clinical data provided were analyzed from file F-200, and its relationship with the CT values (cycle threshold). Results: Of 366 doctors diagnosed with COVID-19 in the La Libertad Region, only 108 were by RT-PCR. The most frequent comorbidities were obesity (13%), cardiovascular disease (10.2%), and asthma (7.4%). Only 26.9% of the physicians received supplemental oxygen, of which 16.7% required mechanical ventilation. The main clinical findings were cough (73.1%) and sore throat (48.1%). 17.6% of the cases were severe. The deceased patients were 5 (4.6%) of which none showed a high CT value. Conclusion: The behavior of the SARS- COV2 infection is related to the CT values in RT-PCR tests of the medical health personnel of La Libertad.